Hubungan Perilaku Pengetahuan Gizi, Sarapan Pagi, dan Uang Saku dengan Kebiasaan Jajan Anak Sekolah Dasar Negeri Banjarbaru Kota 3 Tahun 2013 - Agus Rahmadi; Fitria Aningsih; Welly Rakhman; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2014)
School snack food is a problem that needs attention the public, especially parents, educators, and school administrators. School meals and snacks very risky against biological or chemical contamination of the many disturbing health, both short term and long term. Behavior of children to choose snack foods that have bought both positive and negative impacts to the health of the child. There are still many school snacks are not guaranteed health and potentially cause toxicity. This study aims to investigate the correlation of nutrition knowledge, breakfast, and a children’s pocket money with behavioral habits in Elementary school 3 Banjarbaru Municipalities. This research uses the analytical method with cross sectional design and it was conducted on 74 respondents. Based on the results of the statistical test by using the chi-square find correlation of nutrition knowledge with behavioral habit of eating snacks (p = 0,001), find correlation of breakfast with habit of eating snacks (p = 0,008) and find correlation of money pocket with habit of eating snacks (p = 0,010). From result of this research can be concluded that find correlation of nutrition knowledge, breakfast, and a children’s pocket money with behavioral habits in Banjarbaru Kota 3 Elementary school.